Comparison between Full Endoscopic Lumbar Discectomy (FELD) and Micro Discectomy (MD) in Patients with Lumber Disc Herniation in Terms of Pain Relief and Functional Outcome - Inam, Shahzad; Talha, Muhammad; Shamim, Babar; Qasmi, Shahzad Ahmed; Ali, Sajid; Awan, Liaqat Mahmood (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare pain control and functional outcome in fully endoscopic lumbar discectomies verses open discectomies in local population. Study Design: Quasi-experimental study Place and Duration of Study: Department of Spine Surgery, Combined Military Hospital Rawalpindi, Pakistan from October 2023 to March 2024 Methodology: Study included 200 patients divided into two groups of 100 each; Group-A endo discectomy group and Group-B open discectomy group. In Group-A patients underwent endoscopic lumbar discectomy (both transforaminal and inter laminar) while in Group-B open micro discectomy was performed. Pain relief in the patients was assessed using Numerical Rating Scale (NRS) and OSWESTRY Disability Index (ODI) at immediately post-op, at the time of discharge and at 6 weeks post-op follow-up. Functional outcome was assessed in terms of patient satisfaction at 6 week post-op follow-up. Results: There were 140(70%) male and 60(30%) females. The mean age was 37.61±9.57 and 38.59±9.71 years in Group-A and B respectively. Intergroup comparison yields significant difference (p<0.001) of NRS in Group-A compared to Group-B at immediately post-op and at the time of discharge. Similarly, the ODI score also revealed significant improvement (p<0.001) in Group-A compared to Group-B at immediately post-op and at the time of discharge. Patient satisfaction level was significantly higher in Group-A as compared to group B. Conclusion: Endoscopic spine surgical technique is a wonderful addition in the field of spine surgery. When performed by experienced hands, there is not only speedy recovery but also reduced hospital stay with minimal morbidity and more patient satisfaction.